Fonologi Dalam Konteks Puisi Untuk Menyajikan Materi Pembelajaran Yang Menarik dan Menginspirasi - Anwarsani Anwarsani; Markiah Markiah; Wiwin Muliani; Lynet Lynet; Perasi Perasi; Nabila Salwa; Levi Al Kausar (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
The aim of this article is to delve into the understanding of how phonology can be a key factor in unlocking the meaning and beauty of poetry. By exploring the role of phonology, readers will be introduced to the often-overlooked dimension of sound in the interpretation of poetry. Additionally, the article contributes innovative and engaging teaching strategies, focusing on phonology instruction within the context of poetry. Each presented strategy is expected to enhance the material's appeal, making the learning experience more captivating for students.